Relationship between age, scrotal circumference, postweaning weight and semen quality in Nellore and Caracu bulls: a cross sectional study - Pagoto, Jaine Martelo [UNESP]; Benfica, Lorena Ferreira [UNESP]; Borges, Marcelo Sant’Ana [UNESP]; Ligori, Viviane Andrade [UNESP]; Canesin, Roberta Carrilho; Mercadante, Maria Eugênia Zerlotti [UNESP]; Monteiro, Fabio Morato [UNESP] (Springer Nature, 2023)
The aim of this study was to investigate the relationship between age, scrotal circumference, postweaning weight and semen quality in Nellore and Caracu bulls selected for postweaning weight. Data from the andrological evaluation of 836 bulls born between 2000 and 2019, including 583 Nellore animals (Bos indicus) and 253 Caracu animals (Bos taurus), were used. The bulls were divided into categories of age at the time of assessment: category 1 consisted of animals aged 20 to 23 months (22 ± 0.76 months, 518 ± 94.17 kg), category 2 consisted of animals aged 24 to 35 months (30 ± 4.42 months, 679 ± 137.19 kg), and category 3 consisted of animals ≥ 36 months (60 ± 14.12 months, 907 ± 161.73 kg). The statistical model included the effects of breed, age category, date of semen collection, and breed x age category interaction. Heritability estimates for scrotal circumference at 13 months of age (SC1year) and semen quality traits were obtained for the sample of Nellore animals. Most semen quality traits improved with increasing age in both Nellore and Caracu animals. High heritability was observed for SC1year (0.45), while sperm motility, vigor, turbulence, and major, minor and total sperm defects exhibited low heritability (0.11, 0.019, 0.047, 0.017, 0.017 and 0.019, respectively). Spearman correlations of breeding values for postweaning weight (W378) and SC1year with the semen quality traits were low. Nellore and Caracu bulls have similar semen quality that improves with increasing age. In the Nellore breed, the heritability of SC is high, while semen quality traits exhibit low heritability. Selection for higher postweaning weight does not phenotypically affect the semen quality of bulls at breeding age.
Keywords: Andrological traits; Breeding values; Bull; Heritability; Weight